SUSCEPTIBILITY OF POTATO TUBER MOTH, PHTHORIMAEA OPERCULELLA (ZELLER) TO CIPC (CHLORPROPHAM) - chandel, R S; Bhatia, Deepika; Singh, Brajesh; Chandla, V K (Potato Journal, 2013)
CIPC is normally used for sprout inhibition in stored potatoes meant for processing and table purposes. This compound has been tested as a substitute for chemical pesticides in integrated management of phthorimaea operculella in potato stores. The effect of cipc against different stages of p. operculella was evaluated through bioassays. The relative susceptibility of various stages of p. operculella was studied by topical application in the laboratory at 26Â°c incubation. LC50 of CIPC to eggs was 0.0359%. The susceptibility of CIPC decreased with increasing larval age. The LC50 increased from 0.0398% for neonate larvae to 0.0487%, 0.0512%and 0.0795% for second, third and fourth instar larvae, respectively. pupa was found more susceptible as compared to fourth instar larvae with LC50 of 0.0500%. CIPC was found highly effective against p. operculella adults. There was 100.0% mortality of adults released on CIPC (0.06%) treated tubers in glass jars. The persistence studies revealed 25% mortality of adults after 7 days of treatment. after two months of storage, there was no potato tuber moth infestation in tubers treated with CIPC (0.06%) as compared to 84% in control. CIPC completely stopped the development of sprouts up to a period of two months. with larvae already in tubers, the cipc was extremely effective, with a success rate of 100%. These results indicated good prospects of CIPC application for management of potato tuber moth in country stores.